PATHOPHYSIOLOGICAL CHANGES IN LUNGS OF RAT EXPOSED TO FOUNDRY ENVIRONMENT - R. B.MORE; C. B. JAWALE; V. A. SAWANT; R. S. DUBAL (The Bioscan, 2011)
Foundry industry is characterized by multitude of concomitantly occurring exposures such as silica dust, metal dust, various chemicals, noise, heat, radiations etc. Animal model Rat exposed to foundry environment showed pathophysiological changes. Aim of the experiment was to determine the effects of foundry environment on pathophysiological changes in lungs. Male albino rats were exposed in foundry environment for period of 8h, 16h and 24h. It was observed that increase in alveolar congestion leading to reduction in alveolar space, increased thickening of alveolar wall and blood vessels were according to increase in period of exposure as compared to normal.